2018
DOI: 10.1103/physreve.98.033118
|View full text |Cite
|
Sign up to set email alerts
|

Solutal convection in porous media: Comparison between boundary conditions of constant concentration and constant flux

Abstract: We numerically examine solutal convection in porous media, driven by the dissolution of carbon dioxide (CO2) into water-an effective mechanism for CO2 storage in saline aquifers. Dissolution is associated with slow diffusion of free-phase CO2 into the underlying aqueous phase followed by density-driven convective mixing of CO2 throughout the water-saturated layer. We study the fluid dynamics of CO2 convection in the single aqueous-phase region. A comparison is made between two different boundary conditions in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 93 publications
6
56
0
Order By: Relevance
“…Therefore, the rock‐fluid interactions stimulate the instabilities. The provided results are in‐line with recent experimental (Rasmusson et al, ) and numerical (Amooie et al, ) studies, which suggest tc=1Ran.H2De and calculated n=1.1427 and n=1.14, respectively. Figure b provides the downward movement of carbon concentration for a fixed time ( t=4 years) for different Rayleigh numbers.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the rock‐fluid interactions stimulate the instabilities. The provided results are in‐line with recent experimental (Rasmusson et al, ) and numerical (Amooie et al, ) studies, which suggest tc=1Ran.H2De and calculated n=1.1427 and n=1.14, respectively. Figure b provides the downward movement of carbon concentration for a fixed time ( t=4 years) for different Rayleigh numbers.…”
Section: Resultssupporting
confidence: 91%
“…Density‐driven convective flow is ubiquitous in natural systems, such as water infiltration into soil (Assouline, 2013), atmospheric movement (Hodges & Thorncroft, 1997) and oceanic currents (Ruddick & Gargett, 2003). Density‐driven convection has an wide application for flow in porous media, including geothermal energy production (Cheng & Minkowycz, 1977), oil separation from sand (Taylor, 2018), and carbon dioxide sequestration (Amooie et al, 2018; Mahmoodpour et al, 2019). It is well identified that when dense fluid sits above less dense fluid due to solute concentration and/or temperature, the system is easy to lose its equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…convection in a container heated from below and cooled from above, and it has been studied extensively over the last few decades (Ahlers, Grossmann & Lohse 2009;Chillà & Schumacher 2012;Xia 2013). Also the related problem of convection in a fluid-saturated porous medium has received increasing attention owing to its importance in a wide range of natural and industrial processes, such as geothermal energy recovery and geological sequestration of carbon dioxide (Hassanzadeh, Pooladidarvish & Keith 2007;Cinar, Riaz & Tchelepi 2009;Orr 2009;Huppert & Neufeld 2014;Emami-Meybodi & Hassanzadeh 2015;De Paoli, Zonta & Soldati 2016;Soltanian et al 2016;Amooie, Soltanian & Moortgat 2018). It is indeed of both fundamental and practical interest to study RB convection in porous media, and considerable progress has been achieved over the years based on the combinations of experimental, numerical and theoretical studies (Lapwood 1948;Wooding 1957;Joseph, Nield & Papanicolaou 1982;Otero et al 2004;Araújo et al 2006;Nield & Bejan 2006;Landman & Schotting 2007;Hewitt, Neufeld & Lister 2012Keene & Goldstein 2015;Wen, Corson & Chini 2015;Ataei-Dadavi et al 2019;Chakkingal et al 2019).…”
Section: Introductionmentioning
confidence: 99%